Maintaining Children's Mental Health: Revealing Teacher Strategies During Offline Learning for Early Childhood - Cahyani, Izdihar Syifa; Khunaifi, Agus (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – School preparation in response to the new government policy for face-to-face learning requires the active roles of teachers and students, particularly concerning children's mental health. The importance of addressing children's mental health during the transition from online to face-to-face learning needs more attention. The purpose of this research is to identify and describe the strategies employed by teachers in maintaining children's mental health during face-to-face learning at Playgroup Jaya Lestari in Kalinyamat Wetan Village, Tegal City. Design/methods/approach – This research adopts a qualitative method with a descriptive approach. Data collection techniques used include observation, interviews, and documentation. The subjects of this research are educators, including principals and teachers. The data analysis techniques applied are data reduction, data display, and verification. To test the validity of the data, source triangulation was used, involving teachers and students at Playgroup Jaya Lestari. Findings – The results indicate that strategies employed by teachers to maintain children's mental health during face-to-face learning include using both individual and group approaches. These strategies emphasize the roles and functions of teachers as inspirers, mentors, and more. Teachers can maintain children's mental health by organizing learning activities that involve play, ensuring children remain happy, cheerful, and free from stress or laziness. These strategies are reinforced through their direct application in teaching and learning activities. Research implications/limitations – The findings highlight the importance of increased awareness of children's mental health, which impacts developmental psychology and the learning process. This research underscores the necessity for educators to focus on mental health early in the educational environment. Practical implications – The research demonstrates the need for effective strategies for teachers to maintain children's mental health during the learning process. It also emphasizes the importance of institutional readiness to address future challenges and the necessity for collaboration with professionals in psychology to tackle early childhood mental health issues. Originality/value – This study provides a new perspective by examining the mental health of children in relation to Early Childhood Development psychology and the role of teachers in this developmental process. Paper type Research Paper